2015
DOI: 10.1007/s12011-015-0409-1
|View full text |Cite
|
Sign up to set email alerts
|

Proanthocyanidin Protects Human Embryo Hepatocytes from Fluoride-Induced Oxidative Stress by Regulating Iron Metabolism

Abstract: To investigate whether grape seed proanthocyanidin extract (GSPE) antagonizes fluoride-induced oxidative injury by regulating iron metabolism, human embryo hepatic cells (L-02) were incubated with sodium fluoride (NaF, 80 mg/L) and/or GSPE (100 μmol/L) for 24 h. Results showed the glutathione peroxidase (GSH-Px) content, superoxide dismutase (SOD) activity, and total antioxidant capacity (T-AOC) level of the NaF group were significantly lower than that of the control group (P < 0.05), while malondialdehyde (MD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…In this study, fluoride may exert a certain impact on iron metabolism, cause iron accumulation in the liver of mouse, eventually leading to liver iron overload. This is supported by our previous in vitro study that fluoride induced iron overload accompanied by increased Hepcidin but decreased FPN expression (Niu et al, 2016). Similarly, Lee et al (2015) demonstrated that excessive iron induced hepcidin activation and FPN degradation in human liver SK-HEP-1 cells, thus resulting in reactive oxygen species (ROS) generation.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…In this study, fluoride may exert a certain impact on iron metabolism, cause iron accumulation in the liver of mouse, eventually leading to liver iron overload. This is supported by our previous in vitro study that fluoride induced iron overload accompanied by increased Hepcidin but decreased FPN expression (Niu et al, 2016). Similarly, Lee et al (2015) demonstrated that excessive iron induced hepcidin activation and FPN degradation in human liver SK-HEP-1 cells, thus resulting in reactive oxygen species (ROS) generation.…”
Section: Discussionsupporting
confidence: 67%
“…In iron overload patients or animals, accumulated iron facilitates the formation of free radical that disrupt the redox balance of the cells, thus causing oxidative stress (Toyokuni, 2011). Although previously we have confirmed that iron overload is involved in fluoride-induced oxidative injury in human embryo hepatocytes (Niu et al, 2016), the in vivo evidence of fluoride-induced oxidative stress resulting from iron overload is still obscure. The results of present study showed an increased total iron content in fluoride-treated mouse liver, suggestive of iron overload.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Kuppusamy and Tan (2011) anticipated a protective effect of deferoxamine against iron mediated oxidative stress along with iron chelator property. Additionally Niu et al (2016) reported that, Q prevents iron-induced oxidative damage in human hepatic cells and endocrinal gland by decreasing iron content and increasing antioxidants, including GPx, SOD, and total antioxidant capacity. David et al (2008) provided evidence that, combined treatment with DFO and Q is capable of decreasing oxidative load on neuronal cell in the striatum as evidenced by an increase in the total GSH and SOD levels.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of Nrf2 can promote the expression of antioxidant genes and induce synthesis of phase II detoxifying enzymes [48]. Studies have shown that Nrf2 plays a crucial role in cellular resistance to oxidation and exogenous damage [49,50]. Recent studies have indicated that activating the Nrf2/ARE pathway has a hepato-protective effect [51,52].…”
Section: Discussionmentioning
confidence: 99%